ARTIFICIAL INTELLIGENCE IN BUREAUCRATIC TRANSFORMATION: AN ANALYSIS OF ITS UTILIZATION AMONG CIVIL SERVANTS IN GOWA REGENCY - Mallappiang, Nasiratunnisaa; Anirwan, Anirwan; Herianto, Dedy; Sumardi, Sumardi (Entrepreneurship Undergraduate Program at Amkop Business School, 2025)
This study aims to analyze the use of Artificial Intelligence (AI) in the completion of the work of the State Civil Apparatus (ASN) in Gowa Regency. The approach used was descriptive quantitative with data collection through questionnaires and semi-structured interviews. The research was carried out from January to March 2025 in several Regional Apparatus Organizations (OPDs) that have adopted digital systems. The results of the study show that most civil servants have utilized AI, especially in simplifying administrative tasks, data processing, and automated reporting systems. The use of AI has been proven to increase the efficiency and productivity of civil servants. However, AI implementation still faces obstacles, such as low digital literacy, limited infrastructure, resistance to work culture, and the absence of comprehensive supportive regulations. This study recommends increasing technical training, strengthening digital infrastructure, and formulating internal policies as strategies to strengthen the use of AI in the government environment. With optimal utilization, AI can become an instrument of bureaucratic transformation that is more adaptive, responsive, and oriented towards high-performance public services.Keywords: Artificial Intelligence, ASN, work efficiency, digital transformation, Gowa Regency